Financial incentives for residential energy efficiency investments in Ireland: Should the status quo be maintained? - Matthew Collins; Seraphim Dempsey; John A. Curtis (The Economic and Social Research Institute (ESRI), 2017)
Improving the energy efficiency of residential dwellings is seen by policy-makers as an important tool to help mitigate the impacts of climate change. Many countries, including Ireland, have put in place policies aimed at stimulating energy efficiency renovations in private households. Options to induce further retrofitting activity include the possibility of altering the structure of financial incentives on offer. At the moment, the Better Energy Homes scheme comprises a cash rebate to home owners following the completion of retrofit works. However, alterations to the incentive structure may be more or less preferred by different segments of the population. We analyse these preferences toward different financing structures. We find that the most preferred option of the choice set presented to respondents is the status quo of a post-retrofit cash rebate, followed closely by the alternative of an upfront discount.
Keywords: 330